Procedimientos contables y administrativos para la contratación de seguros de vida para el personal de un cuerpo de bomberos. - Muñoz Villamar, Guadalupe Yomaira (My University, 2020)
Within the Public Administration, the performance of various elements is understood to generate clear solutions to certain problems, within all processes the established patterns follow a series of regulations and controls that allow regulating their actions. Within this procedure, an important factor is the Internal Control Standards for the Public Sector of the Republic of Ecuador, which constitute general guidelines issued by the Comptroller General of the State, aimed at promoting adequate administration of public resources and determining the proper administrative functioning of the entities. In this sense, the public administration must pursue is basically the realization of the public interest through the operation of a human structure that ensures good administration and its control. The general objective of the present investigation is “To elaborate the accounting and administrative procedures for the contracting of life insurance for the personnel of the Fire Department of the Province of El Oro”, being the methodology used of descriptive character, because the facts They are presented in the way they are given. It is also documentary in nature because the research is based on a vast bibliographic source comprised of books, scientific journals, reports, norms, laws, among others.
Dentro de la Administración Pública, se comprende la actuación de diversos elementos para generar soluciones claras a problemas determinados, dentro de todo proceso los patrones establecidos siguen una serie de normativas y controles que permiten regular sus acciones. Dentro de este proceder un factor importante lo constituyen las Normas Control Interno para el Sector Público de la República del Ecuador, que se constituyen en guías generales emitidas por la Contraloría General del Estado, orientadas a promover una adecuada administración de los recursos públicos y a determinar el correcto funcionamiento administrativo de las entidades. En este sentido, la administración pública debe perseguir es, básicamente, la realización del interés público mediante el funcionamiento de una estructura humana que asegure una buena administración y su control. El objetivo general de la presente investigación es “Elaborar los procedimientos contables y administrativos para la contratación de seguros de vida para el personal del Cuerpo de Bomberos de la Provincia de El Oro”, siendo la metodología empleada de carácter descriptivo, debido a que los hechos se presentan de la forma en que se van dando. También es de carácter documental debido a que la investigación se sustenta en una vasta fuente bibliográfica comprendida por libros, revistas científicas, informes, normas, leyes, entre otras.
Keywords: PROCEDIMIENTOS CONTABLES; SECTOR PÚBLICO; PROCEDIMIENTOS ADMINISTRATIVOS; CONTABILIDAD GUBERNAMENTAL